The effectiveness of STEM-PjBL in enhancing science process skills in Chemistry: A focus on stoichiometrySTEM-PjBL in Enhancing Science Process Skills in Chemistry: A Focus on Stoichiometry - Maulidiningsih Maulidiningsih; Indah Rizki Anugrah; Idha Ayu Kusumaningrum (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2025)
The challenges of 21st-century education require students to develop critical thinking, creativity, and problem-solving skills. Science Process Skills (SPS) are essential in cultivating scientific competence, particularly in chemistry learning. This study investigates the effectiveness of the STEM-Project Based Learning (STEM-PjBL) model in enhancing students’ SPS on the topic of stoichiometry. A quasi-experimental design with a pretest-posttest control group was used, involving 66 tenth-grade students from SMA Islam Al-Azhar 5 Cirebon, equally assigned to experimental and control groups through cluster random sampling. The experimental class was taught using the STEM-PjBL model, while the control class received conventional instruction. Instruments included a validated SPS test and observation sheets. Test data were analyzed using SPSS 26, while non-test data were processed using percentage calculations. Results showed that the STEM-PjBL model significantly enhanced students' SPS, as indicated by a t-test (p = 0.00 < 0.05) and a higher average N-gain in the experimental group (0.574, moderate) compared to the control group (0.274). Improvements occurred across all 11 SPS aspects. Observation data revealed greater student engagement in scientific inquiry, collaborative projects, and scientific practices. These findings confirm that implementing the STEM-PjBL model effectively improves students' science process skills and understanding of chemistry concepts.